On an Algebraic Classification of Multidimensional Recursively Enumerable Sets Expressible in Formal Arithmetical Systems - Manukian, Seda N. (Mathematical Problems of Computer Science, 2021)
Abstract Algebraic representations of multidimensional recursively enumerable sets which are expressible in formal arithmetical systems based on the 1, are introduced and x , S), where S(x) , S), (0,,), (0,, S,signatures(0, investigated. The equivalence is established between the algebraic and logical representations of multidimensional recursively enumerable sets expressible in the mentioned systems.